Both the sera of patients with Behçet's disease and Streptococcus sanguis stimulate membrane expression of hnRNP A2/B1 in endothelial cells. (May 2013) - Cho, SB; Zheng, Z; Cho, S; Ahn, KJ; Choi, MJ; Kim, D-Y; Lee, KH; Bang, D
<x xml:space="preserve">Abstract</x> Objectives: Heterogeneous nuclear ribonucleoprotein (hnRNP) A2/B1 has been identified as a target antigen of anti-endothelial cell immunglobulin (Ig)A antibodies in patients with Behçet's disease (BD). The aim was to investigate the effects of the sera from BD patients and Streptococcus sanguis on the subcellular expression of hnRNP A2/B1 in human dermal microvascular endothelial cells (HDMECs). Method: The sera of BD patients and healthy controls (HC) as well as cultured S. sanguis were used to stimulate HDMECs. Subcellular fractions were obtained from stimulated HDMECs and were subjected to immunoblot analyses. The distribution of hnRNP A2/B1 was investigated by immunocytochemistry and direct immunofluorescence study was performed in biopsy specimens of mucosal ulcers from BD patients. Results: BD patients' sera increased the membrane expression of hnRNP A2/B1 in HDMECs after 12 and 24 h of incubation compared with HDMECs incubated with endothelial cell culture media and HC sera. S. sanguis also increased hnRNP A2/B1 in the cellular membrane. hnRNP A2/B1 mRNA level was also significantly upregulated in HDMECs incubated with BD patients' sera and S. sanguis. Immunocytochemistry demonstrated marked expression of hnRNP A2/B1 in the cytoplasm and cellular membrane of HDMECs incubated with BD patients' sera or S. sanguis. In addition, direct immunofluorescence experiments revealed the co-localization of serum IgA antibodies and monoclonal antibodies (mAbs) against hnRNP A2/B1 in tissue sections from ulcers of BD patients. Conclusions: Our data indicate that both the sera of BD patients with active disease and S. sanguis infection are inflammatory stimuli that can induce membranous hnRNP A2/B1 expression in HDMECs.